What's in it for the observer? Mimetic aspects of learning through observation in simulation-based learning in teacher education. (May 2022) - Frei-Landau, Rivi; Orland-Barak, Lily; Muchnick-Rozonov, Yulia
Abstract: The aim of this exploratory case study was to gain insight into the overlooked learning experience of simulation "observers, " through the lens of the mimetic learning theory. Fifty-nine inservice teachers attended five, 4-h-long simulation workshops. Data were collected using semi-structured interviews (15), a focus group, and participants' reflections (59), and underwent content and linguistic analysis. Four themes denoting mimetic learning emerged: multimodal sensory observation; adopting multiple perspectives; balanced emotional involvement; and cognitive critical thinking. The study highlights the affordances of simulation-based observation experiences in teacher education. This is especially relevant considering the COVID-19 lockdown, when opportunities for peer observation are limited. Highlights: Simulations have been proven effective in teacher learning. The simulation observer experience in the field of education is overlooked. Mimetic learning involves observation, imitation, and practice. Simulation observers' learning experience involve mimetic dimensions. Designing simulation in accordance with these dimesons is imperative.